The effect of caffeine and albuterol on body composition and metabolic rate. (4th August 2015) - Liu, Ann G.; Arceneaux, Kenneth P.; Chu, Jessica T.; Jacob, Gregory; Schreiber, Allyson L.; Tipton, Russell C.; Yu, Ying; Johnson, William D.; Greenway, Frank L.; Primeaux, Stefany D.
<x xml:space="preserve">Abstract</x> Objective Caffeine and ephedrine was an effective combination therapy for weight loss until ephedrine was removed from the market due to safety concerns. This study investigated the combination of caffeine and albuterol as a possibly safer alternative to ephedrine. Methods In a series of experiments using cultured adipocytes, rat models, and humans, the effects of caffeine and albuterol on lipolysis, metabolic rate, food intake, and body composition were evaluated. Results Both caffeine and albuterol enhanced lipolysis in cultured adipocytes. Acute treatment of humans with caffeine and/or albuterol increased resting metabolic rate. Longer‐term studies of rats revealed a trend for increased metabolic rate with albuterol treatment. There was increased lean mass gain concurrent with decreased fat mass gain with caffeine/albuterol treatment that was greater than albuterol treatment alone. Conclusions In rats, albuterol with caffeine produced significantly greater increases in lean body mass and reductions in fat mass without changes in food intake after 4‐8 weeks of treatment. Since caffeine and albuterol are approved for the treatment of asthma in children and adolescents at the doses tested and change body composition without changing food intake, this combination may deserve further exploration for use in treating pediatric obesity.